2006
DOI: 10.1111/j.1365-2133.2006.07150.x
|View full text |Cite
|
Sign up to set email alerts
|

CXC chemokine receptor CXCR4 expression enhances tumorigenesis and angiogenesis of basal cell carcinoma

Abstract: CXCR4 expression may play a critical role in tumour progression and angiogenesis of certain subtypes of BCC with more aggressive nature, and functional blockade of CXCR4 could be a potential therapeutic strategy for these tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 30 publications
(45 reference statements)
2
52
0
Order By: Relevance
“…The proliferation rate and growth patterns of tumors have significant impacts on disease development and prognosis of the patients; indeed, the proliferation rate of tumor cells can indirectly reflect the tumor malignancy (Ravi et al, 1998). Proliferation of malignant cells can be affected by changes in many different proteins, but evidence indicates that the CXCL12-CXCR4 biological axis is important to this process (Chen et al, 2006;Li et al, 2008). We found that, in fact, the proliferation rate of pancreatic cancer cells was significantly increased in the presence of exogenous CXCL12.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation rate and growth patterns of tumors have significant impacts on disease development and prognosis of the patients; indeed, the proliferation rate of tumor cells can indirectly reflect the tumor malignancy (Ravi et al, 1998). Proliferation of malignant cells can be affected by changes in many different proteins, but evidence indicates that the CXCL12-CXCR4 biological axis is important to this process (Chen et al, 2006;Li et al, 2008). We found that, in fact, the proliferation rate of pancreatic cancer cells was significantly increased in the presence of exogenous CXCL12.…”
Section: Discussionmentioning
confidence: 99%
“…47,93,94 Furthermore, anti-human CXCR4 or CXCL12 antibodies also significantly impair metastasis and progression of non-Hodgkin's lymphoma, breast, lung and prostate tumors in animal models. [95][96][97][98] The unique properties of monoclonal antibody (mAb) therapies, including their high affinity and specificity, and the differential expression of target antigen in tumor cells versus normal cells make them attractive agents for cancer immunotherapy. Development of therapeutic mAbs to CXCR4 is challenging due to the fact that CXCR4 can exhibit conformational heterogeneity.…”
Section: Development Antibodies To Cxcr4mentioning
confidence: 99%
“…There is increasing evidence that cancer cells express both chemokines and their receptors allowing both autocrine and paracrine responses, leading to migration, enhanced proliferation and cell survival (Azenshtein et al, 2002;Chen et al, 2006;Zlotnik, 2006). Indeed, metastatic breast cancer cells have been shown to express high levels of the chemokine receptor CXCR4 (Moore, 2001).…”
mentioning
confidence: 99%
“…Chemokines signal through G-protein-coupled receptors on cells inducing cytoskeletal rearrangement, firm adhesion to endothelial cells and directional migration (Zlotnik and Yoshie, 2000). These secreted proteins act in a co-ordinated fashion with cell-surface proteins, including integrins, to direct specific homing of various subsets of haematopoietic cells to specific anatomical sites (Moser et al, 2004).There is increasing evidence that cancer cells express both chemokines and their receptors allowing both autocrine and paracrine responses, leading to migration, enhanced proliferation and cell survival (Azenshtein et al, 2002;Chen et al, 2006;Zlotnik, 2006). Indeed, metastatic breast cancer cells have been shown to express high levels of the chemokine receptor CXCR4 (Moore, 2001).…”
mentioning
confidence: 99%